Synthesis and Formation Mechanism of Limestone-Derived Porous Rod Hierarchical Ca-based Metal–Organic Framework for Efficient CO(2) Capture - Chang, Po-Hsueh (Materials (Basel), 2020)
Limestone is a relatively abundant and low-cost material used for producing calcium oxide as a CO(2) adsorbent. However, the CO(2) capture capacity of limestone decreases rapidly after multiple carbonation/calcination cycles. To improve the CO(2) capture performance, we developed a process using limestone to transform the material into a rod Ca-based metal–organic framework (Ca-MOF) via a hydrothermal process with the assistance of acetic acid and terephthalic acid (H(2)BDC). The structural formation of rod Ca-MOF may result from the (200) face-oriented attachment growth of Ca-MOF sheets. Upon heat treatment, a highly stable porous rod network with a calcined Ca-MOF-O structure was generated with a pore distribution of 50–100 nm, which allowed the rapid diffusion of CO(2) into the interior of the sorbent and enhanced the CO(2) capture capacity with high multiple carbonation–calcination cycle stability compared to limestone alone at the intermediate temperature of 450 °C. The CO(2) capture capacity of the calcined porous Ca-MOF-O network reached 52 wt% with a CO(2) capture stability of 80% after 10 cycles. The above results demonstrated that rod Ca-MOF can be synthesized from a limestone precursor to form a porous network structure as a CO(2) capture sorbent to improve CO(2) capture performance at an intermediate temperature, thus suggesting its potential in environmental applications.